Thermal performance and design parameters investigation of a novel cavity receiver unit for parabolic trough concentrator. (May 2021) - Mohamad, Khaled; Ferrer, P.
Abstract: This paper discusses an improved concept for a cavity receiver unit for Solar Parabolic Trough Collectors (PTC) with the application of hot mirror coating (HMC) on a cavity aperture. This design aims to lessen radiant energy losses while operating at higher temperature by incorporating a variety of optically active layers. The theoretical background is presented, which was derived in previous work, and the resulting implementation in a simulation code. The layout and results of an experiment were discussed, which allowed us to make contact with the simulation with minor adjustments. It was seen that the correspondence between the experiment and simulation results was encouragingly close (Chi squared p > 0.8 and p > 0.95 ), which allowed investigation of simulations of different receiver designs. Simulated outcomes for the temperature of the heat transfer fluid, temperature maps and efficiencies are presented. Our proposal indicates temperature related benefits when compared to other popular designs in terms of the heat transfer fluid temperature and efficiency, which is about 7% higher at temperatures exceeding ∼600 °C. Highlights: A novel design of a receiver unit for a parabolic trough collector. Experimental and theoretical works prove that the design is a strong candidate to reduce the dominant radiant energy losses. Study the effect of hot mirror coating on the aperture of the receiver unit. The design can exceed the efficiency of existing alternatives plagued by similar constraints.